Response of Drosophila suzukii (Diptera: Drosophilidae) to extreme heat and dryness - Eben, Astrid; Reifenrath, Maria (Agricultural and forest entomology, 2018)
Drosophila suzukii Matsumura (Diptera) is a polyphagous herbivore native to East Asia that develops in cultivated and wild fruits. In 2011, it appeared in Germany. In 2012, economic damage was recorded and, in 2014, the harvest of stone and soft fruits was lost in some regions. By contrast, during 2015, populations remained lower. Record temperatures and dryness might have impeded population growth during that year. To test this hypothesis, flies were exposed to a 4-day simulation. We evaluated the effect of fluctuating temperature and humidity on mortality and reproduction of D. suzukii from three age classes (average age: class 1: 3 days; class 2: 11 days; class 3: 20 days). Maximum temperatures were 27, 33 and 39 °C. Relative humidity oscillated between 18% and 85%. Fly mortality through heat stress ranged from 50% to 80%. Higher rates died of oldest flies and females. Offspring per female did not differ between heat stressed and control groups. Flies of both sexes were not sterilized through heat and dryness. Prior acclimation reduced any negative effects. We concluded that heat waves and extreme dryness during 2015 were one cause of the low population densities of D. suzukii observed under field conditions.
First published: 13 May 2017
Gesehen am 09.07.2019